Sustainable Approaches to the Synthesis of Metallophthalocyanines in Solution - Gloria Zanotti (Molecules, 2021)
This work aims to investigate more sustainable reaction conditions for the synthesis of metallophthalocyanines. Anisole, glycerol and their mixtures have been investigated as reaction media for the tetramerization of phthalonitriles. Acetates of three divalent first-transition metal cations, Co(II), Cu(II) and Zn(II), were used and several bases were tested, depending on the chosen substrates and reaction conditions, with a view to making the whole process more sustainable while ensuring its scalability. Unsubstituted phthalocyanines were synthesized to analyze the behavior of the different metal ions in terms of reactivity in the new reaction media, resulting in a general Cu > Co > Zn trend, while the nonpolar tetra-tert-butyl substitution was investigated to evaluate the synthesis of soluble derivatives in the new conditions. Furthermore, the potassium hydroxide (KOH)-aided statistical synthesis of the unsymmetrical 9(10), 16(17), 23(24)-tri-tert-butyl-2-iodophthalocyaninato zinc(II), starting from 4-tert-butylphthalonitrile and 4-iodophthalonitrile in a glycerol/anisole mixture, proceeded with a satisfactory 26% yield. Our results provide insights into the investigation of new reaction environments and the understanding of their strengths and weaknesses, with a view to further increasing the sustainability of the synthesis of metallomacrocycles with high added value while lowering their production cost.